Photodynamic therapy induces human esophageal carcinoma cell pyroptosis by targeting the PKM2/caspase-8/caspase-3/GSDME axis. (1st November 2021) - Li, Lisha; Song, Dongfeng; Qi, Ling; Jiang, Mingxia; Wu, Yiming; Gan, Junqing; Cao, Kui; Li, Yanjing; Bai, Yuxian; Zheng, Tongsen
Abstract: Photodynamic therapy (PDT) uses a photosensitizer (PS) and visible light to induce cancer cell death. Pyroptosis is a new type of programmed cell death that is associated with the gasdermin protein family. However, the precise mechanism of pyroptosis in PDT-induced suppression of esophageal cancer remains unknown. We demonstrate that PDT can induce gasdermin E (GSDME)-mediated pyroptosis, which is characterized by the formation of pyroptotic blebs in esophageal squamous cell carcinoma (ESCC), which burst and release intracellular contents and pro-inflammatory mediators. Mechanistically, PDT may inhibit pyruvate kinase M2 (PKM2) and consequently, activate caspase-8 and caspase-3, which ultimately releases N-GSDME and triggers pyroptosis in ESCC. Moreover, PDT decreased the efficiency of pyroptosis in the presence of a glycolytic inhibitor. Overall, our results show that PDT induces pyroptosis in ESCC by targeting the PKM2/caspase-8/caspase-3/GSDME axis. This is the first in-depth study of the specific mechanism underlying PKM2-mediated pyroptosis under PDT in ESCC, and potentially has great implications for the clinical application of PDT in ESCC. Highlights: PDT can induce pyroptosis in human esophageal carcinoma cells. PDT can induce pyroptosis by targeting PKM2/caspase-8/caspase-3/GSDME pathway. 2-Deoxy-d-glucose has potential for PDT-induced pyroptosis treatment.